Digital Dialects: The Impact of Social Media on Language Evolution And Emerging Forms of Communication - Rini Ekayati; Berlin Sibarani; Siti Aisah Ginting; Rahmad Husein; Teguh Satria Amin (International Journal of Educational Research Excellence (IJERE), 2024)
The advent of social media has profoundly influenced language evolution, introducing novel linguistic trends and emergent forms of communication. This literature review, titled "Digital Dialects: The Impact of Social Media on Language Evolution and Emerging Forms of Communication," explores three primary research problems. First, it investigates how social media contributes to language change. Second, it examines the emergent of new forms of communication. Third, it assesses the positive and negative impacts of social media on language proficiency and literacy. The research aims to analyze the contribution of social media in language change, identifying new forms of communication, and evaluating their impact on language learning and literacy development. Utilizing a documentary design, this study systematically reviews existing literature on the subject, drawing from previous publications to provide a comprehensive overview of the ways in which social media shapes language use. The findings reveal that social media acts as a catalyst for linguistic innovation, while also presenting challenges and opportunities for language proficiency and literacy. This review contributes to a deeper understanding of the dynamic relationship between social media and language, offering insights into the ongoing evolution of communication in the digital age.